Investigation of Mechanical Properties of Coconut Fiber as a Concrete Admixture - Ramli M.S.; Abas N.F.; Othuman Mydin M.A. (MATEC Web of Conferences, 2014)
The high cost of conventional construction materials is the dominating factor affecting housing systems worldwide. Because of this, further research into alternative materials in construction is required. The purpose of this study is to experimentally investigate the physical characteristics and mechanical properties of concrete produced using shredded coconut fibre composites. The following percentage amounts of fibre were tested: 0 % (control), 0.6 %, and 1.8 %. The coconut fibres were cut to a certain length according to previous studies which suggested that the most ideal length is around 30 - 60mm. The test results showed that the compressive strength of concrete decreased as the percentage of total fibre in the concrete mix increased. The experimental results also showed that coconut fibre concrete performed satisfactorily in terms of crack growth in comparison to that of conventional concrete. Finally, it was concluded that the use of coconut fibres has great potential in the production of lightweight concrete or normal concrete for use in the construction of concrete structures. As coconut fibre is a natural material that is easily available and cheap, it is a particularly good, low-cost alternative. Therefore, this material has the potential to overcome the problem of escalating costs in the industry.